Civic Data Education Series: Developing Civic Data Literacies to Serve Communities. Issue 1 (14th October 2022) - Mattern, Eleanor; Rapchak, Marcia
ABSTRACT: This poster introduces the Civic Data Education Series, a collection of openly licensed modules and instructional materials that support the development of learners' civic data literacy. We designed this series for the learner communities of Library and Information Science (LIS) graduate students and library staff, with the goal of equipping library workers to assume civic data intermediary roles. In this poster, we present the meaning of "civic data literacy, " our project's aims and instructional design approach, and resulting materials.